A comparative study of classical and innovative lobbed air diffusers using temperature sensors for thermal environment/comfort in vehicle cabins - Danca Paul; Cernei Alexandru (E3S Web of Conferences)
Thermal comfort within a vehicle cabin is of utmost importance for both safety and user satisfaction. This study evaluates the impact of two air diffuser geometries—the classical and the innovative lobbed air diffusers—on the thermal environment within a car cabin. Experiments were conducted in an automobile-like enclosure within a climatic chamber, using a Dacia Duster dashboard and ventilation system. The system was manually controlled to vary airflow rates. Wireless temperature sensors were placed at strategic positions and levels (head, chest, knees) to monitor temperature variations over six measurement sessions with different ventilation configurations. Results show that both diffuser types effectively maintain a uniform temperature distribution across seating positions and levels. However, the innovative lobbed air diffusers demonstrated superior performance by maintaining slightly lower or comparable temperature, despite higher inlet air temperature. This suggests enhanced air mixing capability, leading to a more consistent and cooler environment, particularly advantageous during warmer conditions. This study highlights the importance of optimizing thermal comfort in vehicle cabins to improve passenger safety and comfort. Further research on long-term performance and energy efficiency is recommended to fully explore the benefits of innovative air diffusers.